Research progress of improving anti-interference ability and precision of infrared gas sensor - LI Yuncheng; LIANG Yongzhi; JIA Wenpei; RONG Xingfu (Gong-kuang zidonghua, 2015)
Factors of inner components and outside environments on anti-interference ability and precision of infrared gas sensor were analyzed. Existing research achievements and progress were discussed about improving anti-interference ability and precision of infrared gas sensor from views of structure of absorption air-chamber, signal processing circuit, concentration conversion algorithm, temperature and pressure compensation algorithms, etc.